How to get the best deal for massive FDI incentives - Karl P. Sauvant; Zbigniew Zimny (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
Countries offer hundreds of billions of dollars for semiconductor, electric vehicles and renewable energy projects, super-charging a global FDI incentives race. This Perspective suggests that countries providing incentives should do that in a manner that results in wider benefits for the host economy, outlining how this can be done.
Keywords: 330